87. Lesion dosimetry in metastatic thyroid cancer treated with 131I: Method and preliminary results. (December 2018) - Richetta, E.; Cutaia, C.; Poli, M.; Lo Moro, G.; Pasquino, M.; Sacco, L.; Codegone, A.; Pellerito, R.E.; Stasi, M.
Abstract : Purpose: 131 I treatment of metastatic thyroid cancer should take into account doses to metastasis for an optimized approach as highlighted by EU 2013/59 Directive. A SPECT-TC dose calculation method is proposed and verified to standardize the operating protocol; patients' preliminary results are shown. Methods: SPECT-TC was calibrated with a phantom (spheres 11.5, 5.6, 1.1 ml, cylinder 130 ml) filled with liquid 131 I (13 MBq/ml). Acquisition (64views, circular-orbit, 256 × 256, Iterative SCAC) on successive days allowed partial volume effects, dead-time and detector radius (25 ÷ 33 cm) corrections to calculate the dose, whose accuracy was verified. For 8 patients after the therapeutic administration and for 2 patients also in pre-therapy phase 4 SPECT-TC (4 ÷ 6, 24, 48, 96 ÷ 144 h) were performed to calculate the dose to 30 lesions (24 bone, 7 lymph node, 6 pulmonary) with the MIRD spheres model. Results: Calibration factors (cylinder 1.4 kcts/MBq) confirmed partial volume effects (130 ml:100%, 11 ml:75%, 5.5 ml:58%, 1.1 ml:6%) and radius dependence ( ∼ 10%). Dead-time strongly influences counts in early acquisition (up to 17 %). Mean accuracy on activity −15% [−9% ÷ −24%] and dose −13 % [−9% ÷ −18%] for volumes larger than 2.5 cc validates the dosimetric method, according to literature (MIRD24). Dose to lesions per activity unit varies among patients (mean ± 1dev.st 26  ± 38, range 0.1 ÷ 189 Gy/GBq) and within the same patient (up to +583 %) and uptake seems to decrease in following treatments: individualized dosimetry is needed. CT-based method is recommended for VOIs segmentation (mean – 4.9% compared to the isocontour threshold one). In-therapy dose values show high differences (up to −126%) compared to pre-therapy results, whose efficacy must be further investigated with more patients also in terms of optimal activity to be administered to simulate the treatment. Conclusions: Lesion dosimetry of metastatic thyroid cancer treated with radioiodine is accurate with SPECT-TC and provides to the physician a fundamental tool to optimize the treatment.